2014
DOI: 10.1371/journal.ppat.1004447
|View full text |Cite
|
Sign up to set email alerts
|

Programmed Ribosomal Frameshift Alters Expression of West Nile Virus Genes and Facilitates Virus Replication in Birds and Mosquitoes

Abstract: West Nile virus (WNV) is a human pathogen of significant medical importance with close to 40,000 cases of encephalitis and more than 1,600 deaths reported in the US alone since its first emergence in New York in 1999. Previous studies identified a motif in the beginning of non-structural gene NS2A of encephalitic flaviviruses including WNV which induces programmed −1 ribosomal frameshift (PRF) resulting in production of an additional NS protein NS1′. We have previously demonstrated that mutant WNV with abolish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
49
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 64 publications
3
49
2
Order By: Relevance
“…This is in contrast to virus grown in mammalian or insect culture, which has shown that viral replication in vitro is not different between viruses lacking PRF/NS19 and those encoding PRF and producing NS19 (Melian et al, 2010;Ye et al, 2012). Our other recent study also found no difference in replication in avian DF-1 cells between WT and PRF-deficient mutant (A30A9) WNV KUN viruses (Melian et al, 2014). Combined together, these results indicate that the role of PRF/NS19 in viral replication may be virus species and perhaps host species specific.…”
Section: Discussioncontrasting
confidence: 72%
See 4 more Smart Citations
“…This is in contrast to virus grown in mammalian or insect culture, which has shown that viral replication in vitro is not different between viruses lacking PRF/NS19 and those encoding PRF and producing NS19 (Melian et al, 2010;Ye et al, 2012). Our other recent study also found no difference in replication in avian DF-1 cells between WT and PRF-deficient mutant (A30A9) WNV KUN viruses (Melian et al, 2014). Combined together, these results indicate that the role of PRF/NS19 in viral replication may be virus species and perhaps host species specific.…”
Section: Discussioncontrasting
confidence: 72%
“…We have also shown that a viral mutant (Stop Mutant) producing a truncated form of NS19, but not deficient in ribosomal frameshift, replicates with the same efficiency in cells of different origin and has a relatively similar virulence in mice to the WT WNV KUN . In combination with previous work (Melian et al, 2010(Melian et al, , 2014, this suggests that the PRF itself (and not the NS19 protein) is important for viral pathogenesis in the mammalian system. Further work in the mosquito and avian hosts using Stop Mutant producing truncated NS19 will determine whether fulllength NS19 is indeed required for viral replication/ transmission in this vector/host system.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations